Hermetically unsealed: lyric genres in the Homeric Hymn to Hermes - Thomas, O. (Oxford University Press, 2018)
The Hymn to Hermes offers a late archaic or early classical viewpoint on genre in lyric poetry. It compares hymns and theogonies to bantering songs at symposia, apparently in a paradox grounded in Hermes’ ability to control transfers across firm boundaries. However, the comparisons have a latent logic: the Hymn to Hermes is itself bantering intertextually with the Homeric Hymn to Apollo; it alludes to the fact that a komos can involve both praise-poetry and (post-)sympotic erotic songs. Moreover, Apollo’s first interaction with the lyre leads him to engage Hermes in a game of verbal banter, which suggests that this ability of the lyre to unite contrasting performance-types will continue under his patronage. In this sense, the Hymn implicitly reflects on its own power to reshape the audience’s attitudes towards music.